Kajian Tentang Hematologi Penderita Plasmodium vivax di Laboratorium Inti Farma Jayapura-Papua - Elieser Elieser; Dais Iswanto (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Malaria due to Plasmodium vivax infection is a species that attacks humans more than other species. The purpose of this study was to determine the hematological description of Plasmodium vivax sufferers in the Inti Farma Jayapura Laboratory for the period January - June 2020. The descriptive study design used malaria examination using the peripheral blood smear method which was examined using a microscope at the Inti Farma Jayapura laboratory during the period January to June of the year. 2020. The results of the hematological examination were analyzed with descriptive statistics and crosstabulation using the SPSS version 25 program. The results revealed that the mean hemoglobin level of patients with vivax malaria was 12.12, the number of erythrocytes was 5.2750 million / miuL, the leukocyte count was 5,500 miuL, and the trombosiy was 303 thousand. / miuL. These findings provide important information for malaria management in general in Kota Jayapura.Key words: Laboratory, Plasmodium vivax, hematology, peripheral blood smear